Family Perspectives on Clinical Research for Pediatric Multiple Sclerosis: Enhancing Equity. (September 2021) - Mandel, Leslie A; O'Donnell, Ellen; Canenguez, Katia; Castro-Mendoza, Paola B; Lotze, Tim; Waubant, Emmanuelle; Weinstock-Guttmann, Bianca; Chitnis, Tanuja
Pediatric new drug trials are federally mandated, but family perspectives in multiple sclerosis (MS) research are limited. Due to MS chronicity and long-term medical system involvement, we obtained family views on research priorities and optimized methods for future studies. Focus groups were convened with families impacted by pediatric-onset MS. Recruitment included those followed by the Network of Pediatric MS Centers, geographically disparate locations, and centers' voluntary election. Study questions included: healthcare experiences, clinical trials perspectives, cognitive/psychosocial/educational outcomes, disease course and disability accrual. All subjects supported future clinical studies. Patients highlighted contribution to knowledge base but were wary of experimental medication and disease-course impeding activities. Parents underscored medication delivery modalities, side-effects, and limiting children's discomfort. All wanted study relevance made explicit. Suggested future study design elements included: providing compensation, limiting assumptions regarding outcome linkages, understanding study-related psychological impacts, and reducing participation burdens. Rare disease research can assist general medicine diagnosis and referral. Variable study designs and explicit rationale may augment participation. Closing the pediatric research gap requires family engagement in the research process.